Bernards hold 50th wedding anniversary (Raton Range Raton, New Mexico, 1986)
Newspaper Article on the 50th Anniversary of Sunny and Clara Bernard.
Master list item #: 27
File location is in the Raton File Cabinet
Keywords: Bernards, Sunny; Bernards, Clara; Condits, Nancy; Condit, Cliff Jr; Stephens, Lind; Stephens, Kevin; Nolte, Eric; Nolte, Amy; Miller, Pam; Miller, Jay; Miller, Andrew; Schulte, Kathryn; Schulte, Paul; Schulte, Steve; Schulte, Tim; Millington, Florence Pierson; Millington, Mikhala; Millington, Rachel; Brown, Randy; Brown, Christy; Brown, Christi; Shea; Monty; Blakley, Arthur; Foster, Ruth Ann; Woodworth, Larry; Woodworth, Regee; Dry, Lora; Dry, Harry; Farney, Teresa; Farney, Scarlet; Schulte, Rob; Schulte, Georgia; schulte, Brian; McGuire, George; McGuire, (Mrs.); Condit, Cliff Sr; Condit, (Mrs.); Gonzales, Larry; Gonzales, Sue; Woodworth, Lil; Holiday Inn; First United Methodist Church; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Santa Fe, New Mexico; Los Alamos, New Mexico; Tucumcari, New Mexico; Norkeville, Virginia; Lubbock, Texas; Colorado Springs, Colorado; Albuquerque, New Mexico